Legal Development of Zakat According to Islam and its Implementation at Ponpes Al Irsyad Bani Thoha Ranca Iyuh, Panongan District, Tangerang Regency - Hery Septiana; Mila Azizah (International Research and Development for Human Beings (IRDH), 2025)
Zakat, as one of the pillars of Islam, plays a fundamental role in creating social justice and the welfare of the community. However, the understanding of the community, including the students, remains diverse and often limited to theoretical aspects, without optimal implementation. This research aims to enhance the understanding of the students, the management of the pesantren, and the surrounding community regarding the laws of zakat, the types of zakat, the provisions of Sharia, and the distribution methods in accordance with the guidelines of the Qur’an and Sunnah. The methods used are lectures, interactive discussions, and case studies on the implementation of zakat in pesantren. The results of the activities indicate an improvement in participants' understanding of zakat law and a growing collective awareness to implement zakat management in a more structured manner within the pesantren environment. A tangible impact of this seminar is the emergence of initiatives from the pesantren to establish an internal zakat management unit, simultaneously serving as an example for the surrounding community. With ongoing support as a follow-up, it is hoped that the pesantren can become a centre for zakat education that not only plays a role in educating but also actively contributes to the economic empowerment of the community